History of Military Cartography 5th International Symposium of the ICA Commission on the History of Cartography, 2014 - Liebenberg, Elri; Demhardt, Imre Josef; Vervust, Soetkin (Publications of the International Cartographic Association (ICA), 2016)
This volume gathers 19 papers first presented at the 5th International Symposium of the ICA Commission on the History of Cartography, which took place at the University of Ghent, Belgium on 2-5 December 2014. The overall conference theme was 'Cartography in Times of War and Peace', but preference was given to papers dealing with the military cartography of the First World War (1914-1918). The papers are classified by period and regional sub-theme, i.e. Military Cartography from the 18th to the 20th century; WW I Cartography in Belgium, Central Europe, etc.